Skip to main content
Solve for c (complex solution)
Tick mark Image
Solve for g_45 (complex solution)
Tick mark Image
Solve for c
Tick mark Image
Solve for g_45
Tick mark Image
Graph

Similar Problems from Web Search

Share

\frac{1}{2}x+3=cog_{45}\left(2x+1\right)
Multiply both sides of the equation by 2x+1.
\frac{1}{2}x+3=2cog_{45}x+cog_{45}
Use the distributive property to multiply cog_{45} by 2x+1.
2cog_{45}x+cog_{45}=\frac{1}{2}x+3
Swap sides so that all variable terms are on the left hand side.
\left(2og_{45}x+og_{45}\right)c=\frac{1}{2}x+3
Combine all terms containing c.
\left(2g_{45}ox+g_{45}o\right)c=\frac{x}{2}+3
The equation is in standard form.
\frac{\left(2g_{45}ox+g_{45}o\right)c}{2g_{45}ox+g_{45}o}=\frac{\frac{x}{2}+3}{2g_{45}ox+g_{45}o}
Divide both sides by 2og_{45}x+og_{45}.
c=\frac{\frac{x}{2}+3}{2g_{45}ox+g_{45}o}
Dividing by 2og_{45}x+og_{45} undoes the multiplication by 2og_{45}x+og_{45}.
c=\frac{x+6}{2g_{45}o\left(2x+1\right)}
Divide \frac{x}{2}+3 by 2og_{45}x+og_{45}.
\frac{1}{2}x+3=cog_{45}\left(2x+1\right)
Multiply both sides of the equation by 2x+1.
\frac{1}{2}x+3=2cog_{45}x+cog_{45}
Use the distributive property to multiply cog_{45} by 2x+1.
2cog_{45}x+cog_{45}=\frac{1}{2}x+3
Swap sides so that all variable terms are on the left hand side.
\left(2cox+co\right)g_{45}=\frac{1}{2}x+3
Combine all terms containing g_{45}.
\left(2cox+co\right)g_{45}=\frac{x}{2}+3
The equation is in standard form.
\frac{\left(2cox+co\right)g_{45}}{2cox+co}=\frac{\frac{x}{2}+3}{2cox+co}
Divide both sides by 2cox+co.
g_{45}=\frac{\frac{x}{2}+3}{2cox+co}
Dividing by 2cox+co undoes the multiplication by 2cox+co.
g_{45}=\frac{x+6}{2co\left(2x+1\right)}
Divide \frac{x}{2}+3 by 2cox+co.
\frac{1}{2}x+3=cog_{45}\left(2x+1\right)
Multiply both sides of the equation by 2x+1.
\frac{1}{2}x+3=2cog_{45}x+cog_{45}
Use the distributive property to multiply cog_{45} by 2x+1.
2cog_{45}x+cog_{45}=\frac{1}{2}x+3
Swap sides so that all variable terms are on the left hand side.
\left(2og_{45}x+og_{45}\right)c=\frac{1}{2}x+3
Combine all terms containing c.
\left(2g_{45}ox+g_{45}o\right)c=\frac{x}{2}+3
The equation is in standard form.
\frac{\left(2g_{45}ox+g_{45}o\right)c}{2g_{45}ox+g_{45}o}=\frac{\frac{x}{2}+3}{2g_{45}ox+g_{45}o}
Divide both sides by 2og_{45}x+og_{45}.
c=\frac{\frac{x}{2}+3}{2g_{45}ox+g_{45}o}
Dividing by 2og_{45}x+og_{45} undoes the multiplication by 2og_{45}x+og_{45}.
c=\frac{x+6}{2g_{45}o\left(2x+1\right)}
Divide \frac{x}{2}+3 by 2og_{45}x+og_{45}.
\frac{1}{2}x+3=cog_{45}\left(2x+1\right)
Multiply both sides of the equation by 2x+1.
\frac{1}{2}x+3=2cog_{45}x+cog_{45}
Use the distributive property to multiply cog_{45} by 2x+1.
2cog_{45}x+cog_{45}=\frac{1}{2}x+3
Swap sides so that all variable terms are on the left hand side.
\left(2cox+co\right)g_{45}=\frac{1}{2}x+3
Combine all terms containing g_{45}.
\left(2cox+co\right)g_{45}=\frac{x}{2}+3
The equation is in standard form.
\frac{\left(2cox+co\right)g_{45}}{2cox+co}=\frac{\frac{x}{2}+3}{2cox+co}
Divide both sides by 2cox+co.
g_{45}=\frac{\frac{x}{2}+3}{2cox+co}
Dividing by 2cox+co undoes the multiplication by 2cox+co.
g_{45}=\frac{x+6}{2co\left(2x+1\right)}
Divide \frac{x}{2}+3 by 2cox+co.